(untitled) (Circe de clásicos y modernos, 2017)
This paper examines the ciceronian invective against P. Clodius in De haruspicum responso, taking into consideration the concept of sturpum meaning the loss of honour as a result of a sexual practice which demeans the integrity of the individual. We will analyse the lexicon associated to the concept of extralimitation as a constitutive element to Cicero’s argumentative strategy. We will argue that a reading of this speech in relation to extant descriptions of the celebration of the Bona Dea Festival reveals that Cicero attempted to represent Clodius as an outsider, someone who does not behave like a vir and true member of the political elite.